TINGKAT PENGETAHUAN DENGAN KETEPATAN PENULISAN PARTOGRAF - Listiyaningsih Listiyaningsih; Hadina Eka Camila (Oksitosin : Jurnal Ilmiah Kebidanan, 2014)
The results of preliminary studies on the accuracy of the writing partographs for students showed that 30 % of students answered correctly and 70 % of all wrong with an average value of 42 . This shows the low accuracy of partographs writing method,whereas at professional worldthat students are required to always be right in writing partographs. The purpose of this research was to determine the relationship of knowledge level with accuracy of partographs writing . The design of this research is cross-sectional analytic approach. The population in this study is 6th semester students ofIbrahimy Midwifery Academy, the sampling technique used is simple random sampling with a sample size of 37 .Whereas, collecting data using a questionnaire . Data were analyzed using rank spearman test with a significant level ( p< α ) . The results showed p < α ( 0.000< 0.01 ) , so the results of this research concluded that there is a correlation between knowledge level and accuracy of partographs writing method. Keywords : Knowledge , Accuracy , Partograph Writing Method ABSTRAK Hasil studi pendahuluan dalam ketepatan penulisan partograf pada mahasiswa didapatkan hasil bahwa 30% mahasiswa menjawab benar semua dan 70 % salah dengan nilai rata-rata 42. Hal ini menunjukkan masih rendahnya ketepatan cara penulisan partograf, sedangkandi dunia profesi nanti mahasiswa diharuskan untuk selalu tepat dalam menulis partograf. Tujuan penelitian ini adalah untuk mengetahui hubungan tingkat pengetahuan dengan ketepatan penulisan partograf. Rancangan dalam penelitian ini adalah analitik dengan pendekatan cross sectional. Populasi dalam penelitian ini adalahmahasiswa semester VI Akademi Kebidanan Ibrahimy, teknik sampling yang digunakan adalah simple random sampling dengan jumlah sampel 37. Pengumpulan data menggunakan kuesioner.Data dianalisis dengan menggunakan uji rank spearman dengan tingkat signifikan (p <α ). Hasil penelitian menunjukkan p<α (0,000<0,01), sehingga hasil penelitian dapat disimpulkan bahwa ada korelasi tingkat pengetahuan dengan ketepatan cara penulisan partograf. Kata kunci: Pengetahuan, Ketepatan, Cara Pengisian Partograf